Investigation of the Relationship among Cognitive-Behavioral Avoidance, Dysfunctional Attitude and Hopelessness Levels of Parents Having Children with Special Needs - Murat İskender; Yusuf Oktay Atılgan (Sakarya University Journal of Education)
In this study, the aim is to determine the relationship between cognitive-behavioral avoidance, dysfunctional attitudes and hopelessness levels of parents having children with special needs. The research group consists of 155 parents having children with special needs in Kastamonu. Mean, t test, anova and pearson correlation coefficient analysis techniques were used in the analysis of the data. According to the research findings, significant relationships were found between cognitive-behavioral avoidance, dysfunctional attitudes and hopelessness levels of parents having children with special needs. No significant relationship was found in cognitive-behavioral avoidance, dysfunctional attitude and hopelessness levels according to the marital status of the parents and the sex of their children with special needs. Significant relationships were found in cognitive-behavioral avoidance, dysfunctional attitudes, and hopelessness levels according to the sex of the parents, the place of residence, the level of education of the child with special needs, and educational diagnoses. Hopelessness and dysfunctional attitudes of parents having children with special needs are low whereas; cognitive-behavioral avoidance of parents was found to be above the average.